EXPLORING EDD PROGRAM DIRECTORS’ EXPERIENCES CONCERNING EXTENDED DOCTORAL STUDY DURATION - Buera, Eaman; Castles, Jason (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Recent studies revealed that the phenomenon of extended duration of doctoral study (i.e., study duration exceeding the predetermined program schedule) exists at many universities around the world, and most commonly occur during the dissertation phase. In this study, which was conducted at different universities across the United States, the experiences of directors of Education Doctorate (EdD) programs in which students can extend the dissertation time, were investigated. The study employed a qualitative methodology with a phenomenological approach. Data were obtained through semi-structured interviews and analyzed using thematic analysis. Results highlighted factors relevant to EdD timely completion, and aspects that need to be developed for better dissertation experience and more efficient EdD programs. Research outcomes could be helpful for graduate school leaders and professionals in higher education who could review and adopt policies and practices affecting the dissertation experience. A Recommendation for future research scope was included.